GENDER-SPECIFIC FEATURES OF STRESS COPING STRATEGIES IN ADOLESCENTS - Ko‘chkinova Zulxumor Shohobiddin qizi (Modern American Journals, 2025)
In this article stress conditions among adolescents and the strategies they use to cope with them. The study focuses on identifying the impact of gender on the choice of coping strategies. It was found that boys and girls perceive stress differently and apply various adaptation mechanisms. Psychological diagnostic methods, such as the Lazarus and Folkman Stress Coping Strategies test, were used to collect data. Based on statistical analysis, gender-specific characteristics in coping with stress were revealed. The findings of the study can be useful for school psychologists, parents, and educators in providing psychological support to adolescents.
Keywords: Adolescents, stress, coping strategies, gender differences, psychological resilience, adaptation.